Infuusiohoidot turvallisesti kotona - selvitys älykkään teknologian mahdollisuuksista - Eija Kivekäs; Eija Toppinen; Hannu Kokki; Pekka Mäntyselkä; Ulla-Mari Kinnunen; Juhamatti Huusko; Kaija Saranto (Finnish Social and Health Informatics Association, 2017)
The purpose of the research project titled "Safety at Home and in Institutional Care: Utilizing remote monitoring and smart pump -technology in infusion care" was to identify the profile of patients, who require institutional care for infusion therapy for medical and nutrition management, in district hospital area. The digital technology, monitoring, and action models currently use is mapped. The overall purpose is to study the extended implementation of infusion care at home, utilizing smart technology. The data was collected through interviews and statistics. The aim was to explore how home infusion therapy is used, and how willing health care providers are to change current practices. The results showed that infusion therapy was common at outpatient clinics and quite common at home care. Collaboration with home care and emergency care made the infusion therapy possible at patient's home. The use of smart technology in home care was less usual. The participants were enthusiastic and willing to use smart technology in infusion care and remote monitoring of patients' status.